Broad-spectrum activity of bulevirtide against clinical isolates of HDV and recombinant pan-genotypic combinations of HBV/HDV - Mateo, Roberto; Xu, Simin; Shornikov, Alex; Yazdi, Tahmineh; Liu, Yang; May, Lindsey; Han, Bin; Han, Dong; Martin, Ross; Manhas, Savrina; Richards, Christopher; Marceau, Caleb; et al. (JHEP reports, 2023)
Background & Aims - Bulevirtide (BLV) is a small lipopeptide agent that specifically binds to the sodium taurocholate cotransporting polypeptide (NTCP) bile salt transporter and HBV/HDV receptor on the surface of human hepatocytes and inhibits HDV and HBV entry. As a satellite virus of HBV, HDV virions are formed after assembly of HDV RNA with the HBV envelope proteins (HBsAg). Because both viruses exist as eight different genotypes, this creates a potential for high diversity in the HBV/HDV combinations. To investigate the sensitivity of various combinations of HBV/HDV genotypes to BLV, clinical and laboratory strains were assessed. - Methods - For the laboratory strains, the different envelopes from HBV genotypes A through H were combined with HDV genotypes 1-8 in cotransfection assays. Clinical plasma isolates were obtained from clinical studies and academic collaborations to maximise the diversity of HBV/HDV genotypes tested. - Results - The mean BLV EC50 against HDV laboratory strains ranged from 0.44 to 0.64 nM. Regardless of HBV and HDV genotypes, the clinical isolates showed similar sensitivities to BLV with mean values that ranged from 0.2 to 0.73 nM. - Conclusions - These data support the use of BLV in patients infected with any HBV/HDV genotypes. - Impact and implications - This study describes the potent activity of BLV against multiple laboratory strains spanning all HBV/HDV A-H/1-8 genotype combinations and the most diverse collection of HDV clinical samples tested to date, including HBV/HDV genotype combinations less frequently observed in the clinic. Overall, all isolates and laboratory strains displayed similar in vitro nanomolar sensitivity to BLV. This broad-spectrum antiviral activity of BLV has direct implications on potential simplified treatment for any patient infected with HDV, regardless of genotype, and supports the new 2023 EASL Clinical Practice Guidelines on HDV that recommend antiviral treatment for all patients with CHD.
Gesehen am 12.03.2024